Surgical Treatment of Articular Cartilage Defects in the Knee: Are We Winning? - A. R. Memon; J. F. Quinlan (Advances in Orthopedics, 2012)
Articular cartilage (AC) injury is a common disorder. Numerous techniques have been employed to repair or regenerate the cartilage defects with varying degrees of success. Three commonly performed techniques include bone marrow stimulation, cartilage repair, and cartilage regeneration. This paper focuses on current level of evidence paying particular attention to cartilage regeneration techniques.